PENGARUH SEL EFFICACY DAN LOCUS OF CONTROL TERHADAP KINERJA PEGAWAI DINAS PENDIDIKAN KABUPATEN KERINCI - Sudirman Sudirman; Rio Baviga (Jurnal Bina Bangsa Ekonomika, 2024)
This research aims to find out: 1. Whether Self Efficacy and Locus of Control have a partially simultaneous effect on the performance of Kerinci Regency education service employees. 2. How much influence does Self Efficacy and Locus of Control have on the performance of Kerinci Regency education service employees. This research was conducted at the Kerinci Regency Education Office. The data used is primary data and secondary data, the analysis method used is multiple linear analysis with the help of the SPSS version 22 program. Based on the results of the research, it shows that: There is a positive and significant influence between self-efficacy (X1) partially on the performance of employees (Y) of the Kerinci Regency Education Service as evidenced by the calculated t value > t table (4.143 > 2.030) with a significant value (0.000 < 0 .05). There is no significant effect between locus of control (X2) partially on the performance of employees (Y) of the Kerinci Regency Education Office as evidenced by the calculated –t value < t table (- 2.753 < 2.030) with a significant value (0.009 < 0.05) so Ho rejected and H2 accepted. There is a positive and significant influence between self-efficacy (X1) and locus of control (X2) simultaneously on the performance of employees (Y) of the Kerinci Regency Education Office as evidenced by the calculated F value > F table (60.753 > 3.26) as well as with a significant value (0.000 < 0.05) then Ho is rejected and Ha is accepted, meaning that simultaneously there is a significant influence between self-efficacy and locus of control on the performance of Kerinci Regency Education Office employees. The magnitude of the influence of self-efficacy and locus of control simultaneously on the performance of Kerinci Regency Education Service employees is 77.10% while the remaining 22.90% is influenced by variables not studied